The derived source in Arabic grammar - Khalaf, Aqeel Hassen (Thi Qar Arts Journal, 2024)
The derived noun is considered one of the important topics in Arabic grammar, yet it has not been studied thoroughly, especially in terms of semantics, the differences between the derived noun particles, and the difference between the explicit and derived noun. This research sheds light on the derived noun particles that have found differences among grammarians; they differed in their number, with some considering "al-ladhi" as one of the derived noun particles, while excluding the equalizing hamza, which is clearer in its indication of the derived noun than others, as will be clarified during the research.The semantics of the derived noun is a very important topic in grammatical studies, yet it has not received sufficient attention in semantic research and studies in extensive grammatical works. It has been largely overlooked, with only a few scattered mentions in books, appearing like an unstrung necklace and an incoherent whole.